Factors Influencing Acceptance of Tourism Academia Towards Implementation of New-Normal Policy in Tourism Industry; Evidence from Bali - Anom Hery Suasapha; Ni Made Eka Mahadewi; Ida Bagus Gede Agung Widana; Diah Cynthia Putri (Centre For Tourism Planning and Development, 2021)
This article aims to understand factors that influence the acceptance of tourism academia toward the implementation of a new-normal policy for the tourism industry in Bali. Data were collected from an online survey. The population from which the sample was derived was the tourism lecturers of Bali Tourism Polytechnic. The sample size was 88, representing a population of 151 lecturers. It corresponds to the statistical power of 0,90. Statistical descriptive analysis and multiple linear regression analysis were performed to analysis the data. The result of the research shows that acceptance of tourism academia toward implementation of the new-normal policy was simultaneously influenced by their perception of the impact caused by the pandemic to the industry as well as their perception about the dangerous disease itself, even though partially, the impact of the pandemic seems to be the stronger influencing factor compared to their perception about the dangerous disease. The article concludes that tourism academia accepted the opening of the tourism industry while stressing that the opening should be accompanied by strict implementation of the new-normal protocol, to prevent the second wave of the pandemic COVID-19 as well as to prevent future irreversible damages to the tourism industry in term of its safety and security image.